Ohio, USA. Monumentale Zeremoniallandschaften der Hopewell-Kultur - Komp, Rainer (e-Forschungsberichte des DAI, 2017)
A four-year collaboration between the German Archaeological Institute and the Hopewell Culture National Historical Park, Ohio, USA aims in a “fencelineto-fenceline” geomagnetic survey of all park property, and will permit additional survey at other native american Hopewell ceremonial earthworks such as the Ohio History Connection’s Newark Earthworks and Fort Ancient. The new magnetic data reveal multiple wooden post circles, ditched enclosures, plazas and avenues that were entirely unexpected. An extensive pit cluster may lead to the long-sought discovery of Hopewellian camp sites. The project will stimulate the sites’ development for public awareness and foster their candidacy for a listing as World Heritage Monument.